SAT0069 Abnormal bone and cartilage metabolism could be antagonised by pulsed electromagnetic fields (PEMFS) and tnf-Α and il-6 gene knockouts in a similar mechanism. (12th June 2018) - Zhu, S.Z.; He, H.; Wang, Q.; Wang, D.; Wang, H.; Gao, C.; Zhang, C.; Yu, X.; He, C.
Abstract : Background: Pulsed electromagnetic fields (PEMFs), as a safe and non-invasive method, could positively affect bone and cartilage metabolism. However, the effect and underlying mechanisms of PEMFs on osteoporosis and osteoarthritis remain poorly understood. Objectives: The present study is designed to investigate the effect of PEMFs on osteoporotic bone and degenerative cartilage together with its potential molecular mechanisms in mice with different gene background. Methods: Twenty 12 week male and Female wild-type (WT), TNFα knockout (TNFα -/- ) or IL6 knockout (IL6 -/- ) mice, respectively, were sham-operated (SHAM) or subjected to destabilisation of the medial meniscus (DMM) and ovariectomy (OVX) surgeries. After surgeries, WT mice were equally assigned to the non-treatment and PEMFs groups. Mice in PEMFs group were subjected to daily 1 hour PEMFs exposure with 8 Hz, 3.8 mT (peak value). Then all mice were euthanized after 4 weeks. Bone mass and subchondral microarchitecture were determined using micro-CT. Bone and cartilage metabolism was assessed by histological analysis, serum analyses, qRT-PCR and Western-Blot. Results: The surgical models of osteoporosis and osteoarthritis were proved successful evidenced by the analysis of micro-CT data and histological analysis. The bone loss and damaged cartilage were largely repaired by TNFα and IL6 gene knockout and partially inhibited by PEMFs exposure. Interestingly, no difference in Micro-CT data analysis was found between PEMFs group and gene knockouts, although a slight increase could be observed in TNFα -/- mice when compared to the PEMFs group. Negative effects on bone and cartilage was proved by testing key cytokines in anabolism and catabolism. PEMFs treatment and gene knockouts corrected the negative effects by targeting mediators in molecular pathways like Wnt and RANK. The differences in mRNA and protein level changes between PEMFs and gene knockouts were minor. Conclusions: PEMFs alleviated surgeries induced bone loss and cartilage degeneration by promoting anabolism and inhibiting catabolism possibly in a similar mechanism to TNF-α and IL-6 gene knockouts, which imply that TNF-α and IL-6 may become new potential targets for PEMFs in treating degenerative bone diseases. References: [1] Kapoor, Mohit, et al. "Role of proinflammatory cytokines in the pathophysiology of osteoarthritis."Nature Reviews Rheumatology2011;7(1):33. [2] Redlich, Kurt, Josef S. Smolen. "Inflammatory bone loss: pathogenesis and therapeutic intervention."Nature reviews Drug discovery2012;11(3):234. [3] Zhu, Siyi, et al. "Effects of pulsed electromagnetic fields on postmenopausal osteoporosis."Bioelectromagnetics2017. Acknowledgements: This work was supported by Grants from National Natural Science Foundation of China (No. 81572639 and 81770875 to X Yu, 81372110 and 81572236 to CQ He), the Chengdu Bureau of Science and Technology No. 2014 -HM01–00382-SF to X Yu, 2015 -HM02–00042-SF to CQ He). We thank our colleagues from the Core Facility of West China Hospital for their consultation and technical guidance. Disclosure of Interest: None declared